ANALISIS KEUNTUNGAN USAHA KERIPIK PISANG GOROHO STUDI KASUS PADA USAHA SANGKAKALA HOME INDUSTRY DI KOTA TOMOHON (Profit Analysis of Goroho Banana Chips Case study on home industry's Trunkle Busines in Tomohon City) - Tracy Triani Toniga; Melisa Taroreh; Ribka M. Kumaat (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to analyze the benefits of goroho banana chips in the home industry of Sangkakala in the city of Tomohon.. The data used in this study were primaryÂ and secondary data were obtained through direct interviews to owner home industry's trunkle busines in tomoho city. Analysis of The data collected in this studyÂ by using profit analysis, and Â Analysis of Revenue Cost (R/C). Based on the results of the study, it can be concluded that the home industry trumpet business in producing goroho banana chips in August 2021 incurred production costs of Rp. 3,838,335, generating revenues of Rp. 4,940,000 and obtaining a profit of Rp. 1,101,665 so that in the analysis The cost ratio obtained an R/C of 1.28, which means that the Goroho Trumpet Home Industry's banana chips business is profitable.